Indonesian L2 learners’ listening anxiety and socio-affective listening strategy: A survey study - Chriswiyati, Eunike Putri; Subekti, Adaninggar Septi (Englisia Journal, 2022)
The present study was conducted to investigate the possible interaction between the second language (L2) learners' listening anxiety and their use of socio-affective listening strategies (SALS). The participants of this study were 74 university learners from non-English departments at a university in Java, Indonesia. The study used the survey method of distributing Google Form questionnaires. Through descriptive statistics, the study found that generally, learner participants had a medium level of listening anxiety. The participants also reported a high level of SALS. Through correlation formula, the study further found that learners’ use of SALS correlated negatively with their listening anxiety. It indicated that the more they used SALS, the lower their listening anxiety tended to be. The correlation was not significant. Based on the findings of the study, several pedagogical implications were suggested. This included promoting more learner-centred activities where learners could develop their socio-affective strategies and giving emphasis on overall comprehension rather than specific grammatical aspects in L2 listening activities. Possible directions for future studies were also suggested concerning the study's findings and possible limitations.